Tindak Tutur Ilokusi pada program Catatan Najwa di YouTube - Putri Ramadhani, Melani; Hermaliza, Hermaliza (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
The phenomenon found in the speech carried out by the host and resource person on the Najwa Note program on Youtube with the theme "The Difficulty of Being a Woman" very much uses illocutionary speech acts. The problem of this research is how is the illocutionary speech act contained in the Najwa Note program on Youtube? . This study aims to describe the illocutionary speech acts contained in the Najwa Note program on Youtube. The approach in this study is a qualitative approach using content analysis methods. The data in this study are all the speech of the host and resource persons which include illocutionary speech acts. Data collection techniques use documentation techniques, listening techniques, and recording techniques. Of the five forms of illocutionary speech acts, only four speech acts were found, namely assertive speech acts, directive speech acts, expressive speech acts, and declarative speech acts. Commissive speech acts were not found in this study.